2003
DOI: 10.1074/jbc.m304265200
|View full text |Cite
|
Sign up to set email alerts
|

NMR Study on the Structural Changes of Cytochrome P450cam upon the Complex Formation with Putidaredoxin

Abstract: We investigated putidaredoxin-induced structural changes in carbonmonoxy P450cam by using NMR spectroscopy. The resonance from the ␤-proton of the axial cysteine was upfield shifted by 0.12 ppm upon the putidaredoxin binding, indicating that the axial cysteine approaches to the heme-iron by about 0.1 Å. The approach of the axial cysteine to the heme-iron would enhance the electronic donation from the axial thiolate to the heme-iron, resulting in the enhanced heterolysis of the dioxygen bond. In addition to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
58
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 68 publications
11
58
0
Order By: Relevance
“…For the wild type enzyme, the signal x at Ϫ1.29 ppm, which is derived from the 9-methyl group of D-camphor, was shifted to the upfield region with increasing concentrations of Pdx red (Fig. 5, left panel), as observed at 40°C (6). In sharp contrast to the wild type enzyme, a new signal at Ϫ1.45 ppm appeared and increased its intensity with a decrease in the intensity of the signal x at Ϫ1.35 ppm upon the addition of Pdx red to the L358P mutant (Fig.…”
Section: Heme Environment Of the Ferrous-co Form Of L358p-up-mentioning
confidence: 74%
See 4 more Smart Citations
“…For the wild type enzyme, the signal x at Ϫ1.29 ppm, which is derived from the 9-methyl group of D-camphor, was shifted to the upfield region with increasing concentrations of Pdx red (Fig. 5, left panel), as observed at 40°C (6). In sharp contrast to the wild type enzyme, a new signal at Ϫ1.45 ppm appeared and increased its intensity with a decrease in the intensity of the signal x at Ϫ1.35 ppm upon the addition of Pdx red to the L358P mutant (Fig.…”
Section: Heme Environment Of the Ferrous-co Form Of L358p-up-mentioning
confidence: 74%
“…It is likely that tighter binding to Pdx in the L358P mutant might be caused by the structural rearrangements at the Pdx-binding site, which optimize the interaction between the L358P mutant and Pdx. Because previous reports (6,15,31) indicated that Pdx induces the structural changes in P450cam through the hydrogen bond between one of the heme propionates and Arg-112 at the putative Pdx-binding site, the structural changes around the heme could also evoke the structural changes in the Pdx-binding site. Therefore, we suggest that the Pdx-binding site of the L358P mutant as well as the heme environment correspond to the Pdx-bound wild type enzyme.…”
Section: Heme Environment Of the Ferrous-co Form Of L358p-up-mentioning
confidence: 99%
See 3 more Smart Citations